If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 61 = 7(1 + 8m) + -1(m + 1) 61 = (1 * 7 + 8m * 7) + -1(m + 1) 61 = (7 + 56m) + -1(m + 1) Reorder the terms: 61 = 7 + 56m + -1(1 + m) 61 = 7 + 56m + (1 * -1 + m * -1) 61 = 7 + 56m + (-1 + -1m) Reorder the terms: 61 = 7 + -1 + 56m + -1m Combine like terms: 7 + -1 = 6 61 = 6 + 56m + -1m Combine like terms: 56m + -1m = 55m 61 = 6 + 55m Solving 61 = 6 + 55m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-55m' to each side of the equation. 61 + -55m = 6 + 55m + -55m Combine like terms: 55m + -55m = 0 61 + -55m = 6 + 0 61 + -55m = 6 Add '-61' to each side of the equation. 61 + -61 + -55m = 6 + -61 Combine like terms: 61 + -61 = 0 0 + -55m = 6 + -61 -55m = 6 + -61 Combine like terms: 6 + -61 = -55 -55m = -55 Divide each side by '-55'. m = 1 Simplifying m = 1
| c=5/9(59-39) | | 3(8x+1)=12(1+2x)-9 | | -4(8k+4)-5(3k-8)=71 | | N-33=66 | | x^2+8x+q=0 | | 93+x+5=180 | | 8(8p-8)=192 | | 4x-30+60-2x=180 | | 15x+5=2(x+7)+13x | | -168=2(8p-7)+6p | | 5x+3y=650 | | -24=4n-8 | | F(3)=-7x+14 | | 16=4(b-3)+7(4+4b) | | -12x=5x+3 | | 180=3x-6+3x-6+2x | | 0.4x+0.1=4.5 | | 5y-7=63 | | 7(4n+4)=-140 | | 6b-1=50 | | log(4)(6-2x)=1 | | 15x+9=-15x+20 | | 130+134+x=180 | | 3n-9=30 | | 8=7+15x+3x+9x | | 2x+4-7y=0 | | 85=7-3(-2+3n) | | 6h+9t=59 | | 3(2x-4)+12=-6 | | 4(6x-7)(4x+7)=0 | | 2x+18=-6x+14 | | 8=15x+7+3x+9x |